Analysis of lightweight box structure / Mohd Alimin Che Ali - Che Ali, Mohd Alimin (2002)
The objective of this project is to examine the behavior of lightweight box structure loaded by given external force. The analysis involves stress, strain and the displacement. There are two methods that have been used to analyze this structure, theoretical analysis and followed by experiment. The experimental result and the theoretical result will be compared. The experimental method used the strain gauge and data logger to obtain the stress occurs. The strain gauges are distributed at several points. The deflection is measured using the dial indicator. The comparison is made based on the result of these two methods. We identify that the theoretical method and experiment show close result.